2019
DOI: 10.1002/jcsm.12488
|View full text |Cite
|
Sign up to set email alerts
|

Divergent skeletal muscle mitochondrial phenotype between male and female patients with chronic heart failure

Abstract: Background Previous studies in heart failure with reduced ejection fraction (HFrEF) suggest that skeletal muscle mitochondrial impairments are associated with exercise intolerance in men. However, the nature of this relationship in female patients remains to be elucidated. This study aimed to determine the relationship between skeletal muscle mitochondrial impairments and exercise intolerance in male and female patients with HFrEF. Methods Mitochondrial respiration, enzyme activity, and gene expression were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…There were no complications or adverse events with this procedure. One piece of muscle sample was immediately placed in 1 mL of ice‐cold specialized preservation solution (BIOPS) for assessment of mitochondrial respiration, while two other portions were divided and rapidly frozen for subsequent histology and molecular analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no complications or adverse events with this procedure. One piece of muscle sample was immediately placed in 1 mL of ice‐cold specialized preservation solution (BIOPS) for assessment of mitochondrial respiration, while two other portions were divided and rapidly frozen for subsequent histology and molecular analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial respiration was assessed in situ from saponin‐permeabilized skeletal muscle fibres using high‐resolution respirometry (Oxygraph‐2K; Oroboros Instruments, Innsbruck, Austria) . Briefly, (i) complex I leak respiration was determined by addition of glutamate (10 mM), malate (0.5 mM), and pyruvate (5 mM) (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial activity in skeletal muscles has long been known to correlate with exercise capacity ( 39 ), with a recent observation showing that especially with respect to complex I ( 43 ), suggesting mitochondrial function is critical for skeletal muscle function. Mitochondrial content has widely been observed to decrease with age in skeletal muscles ( 58 , 78 , 97 ).…”
Section: How Important Is Senescence Of Post-mitotic Cells To Understmentioning
confidence: 99%
“…It is well established that both patients with HF or DM develop mitochondrial dysfunction, which include for example a lower respiratory function and content. 25,[100][101][102] In patients with HFDM, mitochondrial content has been estimated to be lower by 25%, while mitochondrial dysfunction assessed in situ using high-resolution respirometry showed impairments specific to complex I both absolute and when normalized to mitochondrial content, as assessed in the pectoralis major when compared with patients with HF or DM. 25 This finding is important, as it suggests a complex I-specific impairment related to both quality and quantity in patients with HFDM but not HF or DM, and importantly, this was correlated to whole-body measures of exercise intolerance.…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Recent studies have revealed a large, novel, and poorly characterized clinical population of patients with coexistent HF and DM (i.e. HFDM) 16,25–31 . However, our clinical understanding remains limited due to it being unclear whether DM is causal or an associative comorbidity in HF 32 .…”
Section: Does Heart Failure With Diabetes Represent a Distinct Clinicmentioning
confidence: 99%